Pengaruh Promosi Melalui Media Sosial Instagram dan Harga Terhadap Loyalitas Konsumen Pada Konsumen Usaha Mikro Randang Paku Ikan Rangkito Di Kabupaten Dharmasraya - Agnie Ramadhani (CV ODIS, 2023)
This study aimed to ascertain the impact of price and social media advertising on Randang Paku Pangkito customers' loyalty in Dharmasraya Regency. A quantitative descriptive survey is what we're doing here. The participants in this study are Randang Paku Rangkito consumers. The Chocran formula was used to determine the number of research samples. A total of 100 individuals were chosen using the purposive sampling method. The information was gathered by distributing questionnaires with predefined questions to Randang Paku Rangkito customers. Multiple regression analysis using SPSS 21 is the analysis method employed. The study's findings demonstrate that: (1) Instagram social media promotion has a favourable and significant impact on Price has a positive and substantial impact on both consumer loyalty, and (2) price has a positive and significant impact on both consumer loyalty and (3) promotion through social media platforms like Instagram.